Game-Based Learning within the University Program for People with Intellectual Disabilities We are All Campus: Aprendizaje basado en el juego en el programa universitario para personas con discapacidad intelectual Todos Somos Campus (Papeles, 2024)
Introduction: Learning by playing has always been a very desirable didactic proposal. A bridge to fun and pleasure that increases student motivation and engagement. Specifically, board games are highly popular. Methodology: The seventeen students with intellectual disabilities who are members of the Todos Somos Campus University Program of the University of Murcia for the 2022-2023 academic year have participated in this non-experimental quantitative research of an exploratory and evaluative nature. Through a questionnaire, information has been collected about the relevance of sessions with GBL and board games, thus obtaining a real vision of its own protagonists. Results and Discussion: the students are very happy with the development of the sessions. The instructions of the games were clear and understandable, and, in addition, they have allowed them to interact with their classmates, having encouraged help among peers. It is true that differences appear between students who say they like working on the subject of mathematics, who have a better opinion of the overall development of the session and the educational implications that the GBL has. Instead, they all agree that they would like to continue practicing, both inside and outside the classroom, with board games. Conclusions: It is evident that board games are an excellent tool to enhance the development of motor and creative skills, favoring the maturation of social skills, motivation, social interaction, expression of emotions, memory and communication, among others.
Keywords: Intellectual disability; game-based learning; board games; inclusion; university